ANALISIS FISHBONE FAKTOR PENGHAMBAT BELUM TERLAKSANANYA PEMUSNAHAN DOKUMEN REKAM MEDISDI RSI IBNU SINA PADANG - Dian Sari; Maisharoh Maisharoh; Yusmita Yusmita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Medical records that have expired and their usefulness can be destroyed, that is, where the medical records are physically destroyed. RSI Ibnu Sina Padang has not carried out the extermination because of the inhibiting factors of the elements of Man, Money, and Material. This study aims to determine the fishbone analysis of the inhibiting factors that have not been carried out in the destruction of medical record documents at RSI Ibnu Sina Padang. The research was conducted in June 2021 qualitatively with a phenomenological approach. The research was conducted by in-depth interviews with 5 informants, namely the head of the supporting field, the head of the medical records room, and 3 storage officers. Data processing using collaizzi method. The results of the study found that the factors that hindered the implementation of extermination were the lack of human resources to carry out retention accompanied by a team that had not been formed, training on extermination that they had never participated in, and inadequate facilities and infrastructure. Based on the conclusion, it was found that the aspects that hindered the extermination at RSI Ibnu Sina Padang were due to man and material factors. It is hoped that the management will immediately form an extermination team so that SOPs can be applied and training for the team will be carried out which will increase knowledge about the implementation of extermination.